State of pedestrian road safety in Uganda: are interventions failing or absent? - Osuret, Jimmy; Namatovu, Stellah; Biribawa, Claire; Balugaba, Bonny E.; Bayiga Zziwa, Esther; Muni, Kennedy; Ningwa, Albert; Oporia, Frederick; Mutto, Milton; Kyamanywa, Patrick; Guwatudde, David; Kobusingye, Olive (Research Square, 2019)
Background In Uganda, pedestrians are the most frequently injured category of road users, accounting for 40% of road traffic fatalities and 25% of serious injuries every year. There is paucity of information on existing pedestrian interventions and challenges that affect their implementation in Uganda. In this paper, we ascertain the state of pedestrian road safety interventions in Uganda and explore the challenges in the process of design, implementation, monitoring and evaluation of existing interventions. Methods We conducted a qualitative study that started with a desk review of existing policy documents, police statistics, media reports, non-governmental organization reports, and published research. We supplemented the review with 14 key informant interviews and 4 focus group discussions. Participants were drawn from various agencies and stakeholders responsible for road safety. In total, we collected and synthesized data on the design, implementation, and evaluation of pedestrian safety interventions from 25 documents. Data were analyzed using qualitative thematic content analysis. Results The National Road Safety Council within the Ministry of Works and Transport is the lead agency tasked with coordinating all road safety efforts, while the Uganda Police is largely engaged in enforcing pedestrian safety. We identified several existing policies and regulations for pedestrian safety like the Non- Motorized Transport policy whose implementation has been inadequate. Implementation is constrained by weak institutional capacity and limited resources. Moreover, road safety stakeholders operated in silos and this hindered efforts to coordinate pedestrian safety activities. Interventions like road designs were implemented with limited reference to any supporting data and therefore did not cater for pedestrian needs. Conclusion There are interventions targeting pedestrian safety in Uganda, but effective implementation is lacking or failing due to constraints related to weak institutional capacity. This necessitates strategies to mobilize resources to strengthen the capacity of the lead agency to effectively coordinate road safety interventions.
Keywords: Pedestrian; Intervention; Qualitative; Uganda